Modelling and control of a five‐degrees‐of‐freedom pneumatically actuated magnetic resonance‐compatible robot. Issue 2 (26th July 2013) - Jiang, Shan; Feng, Wenhao; Lou, Jinlong; Yang, Zhiyong; Liu, Jun; Yang, Jun
Abstract Background Magnetic resonance imaging (MRI) combined with robotic assistance has the potential to improve on clinical outcomes of biopsy and local treatment of prostate cancer. This paper introduces a pneumatically actuated surgical robotic system for prostatic interventions under MRI guidance. Methods A mechanical dynamics model was established using the Lagrange method and simulated using MATLAB software. A pneumatic actuator model was built through the use of system identification, and stability analysis was proposed based on the Nyquist criterion. In addition, a proportional‐integral‐derivative controller was implemented on the robot for accurate position control. Results Simulation results showed that the steady‐state error of a step response was 0.3 mm and the tracking error of a 1.0 Hz sinusoidal response was 1.5 mm. Experimental results showed that the insertion precision was 0.72 mm in the general laboratory environment. Conclusions The results demonstrated that the robotic system with the designed controller was effective in both position control and trajectory tracking. Copyright © 2013 John Wiley & Sons, Ltd.